Kecukupan Modal, Profitabilitas, Ukuran Perusahaan, dan Return Saham Perusahaan Perbankan di BEI - Pramesti Pramana Putri, I Gusti Ayu Agung; Wirajaya, I Gde Ary (E-Jurnal Akuntansi; Vol 33 No 7 (2023), 2023)
Optimal stock return is one of the main motivations for an investor to invest in an investment. Therefore, companies that have gone public try to always increase the PBV ratio. The aim of this study is to determine and formulate the effect of capital adequacy, profitability, and company size on stock returns. The research population is all banking companies that publish financial reports on the Indonesia Stock Exchange totaling 45 companies. Determination of the research sample was determined by non-probability sampling method with saturated sample technique. Data analysis techniques in this study were tested using multiple linear regression analysis techniques. The results of the analysis show that capital adequacy, profitability, and company size partially have a positive effect on stock returns. The results of the study confirm the signal theory which states that companies voluntarily provide good information to the capital market so that investors want to invest their funds. Keywords: Capital Adequacy; Profitability; Company Size; Stock returns.